Ion Channels as Potential Drug Targets in Dry Eye Disease and Their Clinical Relevance: A Review - Carl Randall Harrell; Vladislav Volarevic (Cells, 2024)
Dry eye disease (DED) is a common multifactorial disorder characterized by a deficiency in the quality and/or quantity of tear fluid. Tear hyperosmolarity, the dysfunction of ion channel proteins, and eye inflammation are primarily responsible for the development and progression of DED. Alterations in the structure and/or function of ion channel receptors (transient receptor potential ankyrin 1 (TRPA1), transient receptor potential melastatin 8 (TRPM8), transient receptor potential vanilloid 1 and 4 (TRPV1 and TRPV4)), and consequent hyperosmolarity of the tears represent the initial step in the development and progression of DED. Hyperosmolarity triggers the activation of ion channel-dependent signaling pathways in corneal epithelial cells and eye-infiltrated immune cells, leading to the activation of transcriptional factors that enhance the expression of genes regulating inflammatory cytokine production, resulting in a potent inflammatory response in the eyes of DED patients. A persistent and untreated detrimental immune response further modifies the structure and function of ion channel proteins, perpetuating tear hyperosmolarity and exacerbating DED symptoms. Accordingly, suppressing immune cell-driven eye inflammation and alleviating tear hyperosmolarity through the modulation of ion channels in DED patients holds promise for developing new therapeutic strategies. Here, we summarize current knowledge about the molecular mechanisms responsible for the inflammation-induced modification of ion channels leading to tear hyperosmolarity and immune cell dysfunction in DED patients. We also emphasize the therapeutic potential of the newly designed immunomodulatory and hypo-osmotic solution d-MAPPS™ Hypo-Osmotic Ophthalmic Solution, which can activate TRPV4 in corneal epithelial cells, stabilize the tear film, enhance natural cytokine communication, and suppress detrimental immune responses, an important novel approach for DED treatment.